2009
DOI: 10.1088/1751-8113/42/5/055301
|View full text |Cite
|
Sign up to set email alerts
|

Compatible transformations for a qudit decoherence-free/noiseless encoding

Abstract: The interest in decoherence-free, or noiseless subsystems (DFS/NSs) of quantum systems is both of fundamental and practical interest. Understanding the invariance of a set of states under certain transformations is mutually associated with a better understanding of some fundamental aspects of quantum mechanics as well as the practical utility of invariant subsystems. For example, DFS/NSs are potentially useful for protecting quantum information in quantum cryptography and quantum computing as well as enabling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…From these operators, we can understand how the information of the data qubit is distributed in the encoded state. We note that direct operations on logical qubits in DFS/NS were discussed in [26].…”
Section: Figmentioning
confidence: 99%
“…From these operators, we can understand how the information of the data qubit is distributed in the encoded state. We note that direct operations on logical qubits in DFS/NS were discussed in [26].…”
Section: Figmentioning
confidence: 99%
“…(2),we see that the two bases may be converted from one to another using, for example, the correspodence between the raising and lower operators of the group and the hermitian basis. To be specific, one would expand ρ = r,s ρ rs E rs , and [29] and references therein. )…”
Section: Affine Map From the Dynamical Mapmentioning
confidence: 99%
“…The invariants I 2 , I 3 , and I 4 not only commute with every element of this set, but can also be used to form a representation of the Lie algebra of SU (2) [20]. It has been shown that the encoded, or logical analogues of the Pauli matrices acting on an encoded qubit can be given in terms of these invariants by the relations…”
Section: Three Quditsmentioning
confidence: 99%
“…In addition, the invariant I (α,β) 2 can also be used to perform the generalized exchange interaction between the states |p (α) |q (β) associated with particles α and β since it has been shown in Ref. [20] …”
Section: Three Quditsmentioning
confidence: 99%